Search for the scalar top quark in pp collisions at square root[s] = 1.8 TeV. - Abazov, V; Abbott, B; Abdesselam, A; Abolins, M; Abramov, V; Acharya, B; Adams, D; Adams, M; Ahmed, SN; Alexeev, G; Alves, G; Amos, N; et al. (2002)
We have performed a search for scalar top quark (stop) pair production in the inclusive electron-muon-missing transverse energy final state, using a sample of pp events corresponding to 108.3 pb(-1) of data collected with the D0 detector at Fermilab. The search is done in the framework of the minimal supersymmetric standard model assuming that the sneutrino is the lightest supersymmetric particle. For the dominant decays of the lightest stop, t-->b chi+1 and t-->blnu, no evidence for signal is found. We derive cross-section limits as a function of stop ( t ), chargino ( chi+1), and sneutrino ( nu) masses.